IL-4 and TAL1 in T-cell acute lymphoblastic leukemia : studies on the participation of microenvironmental cues and cell-autonomous alterations in leukemogenesis - Cardoso, Bruno A. (2012)
Tese de doutoramento, Ciências Biomédicas (Ciências Morfológicas), Universidade de Lisboa, Faculdade de Medicina, 2011